Child-Adolescent Perfectionism Scale - Parent Report - Maria del Carmen Bento Teixeira; Ana Telma Fernandes Pereira; António Ferreira Macedo (Psychologica, 2025)
Perfectionism is widely associated with adverse psychological outcomes and mental health problems. This trait can be observed early in infancy, but it is challenging to diagnose in children. The present study aims to adapt and validate a Child-Adolescent Perfectionism Scale Parent Report (CAPS-PR). We used a Portuguese sample (n = 148) of dyads parents and their children. After adjusting the CAPS-Short Form (SF) from a self-report to a proxy-report scale, parents answered the adapted CAPS-PR about their children, and the Multidimensional Perfectionism Scale – 13 (MPS) about themselves. Children (Median age: 8 years) responded to the Child-Adolescent Perfectionism Scale-Short Form (CAPS-SF). Convergent validity was assessed using the CAPS-SF and MPS. Confirmatory factor analysis of the CAPS–PR (Parents) supported the same two-factor structure found in the CAPS-SF (Children): Self-Oriented Perfectionism and Socially-Prescribed Perfectionism, and represented a very good fit to the data (χ2/df = 2.495; CFI = .945; GFI = .922; TLI = .921; RMSEA = .100, p < .001). Additionally, the CAPS–PR demonstrated adequate internal consistency (Cronbach's alpha ≥ .84). Convergent validity revealed positive correlations between SOP-PR and SOP-SF, and SOP-MPS. Temporal stability was satisfactory in both dimensions of CAPS-PR. In conclusion the CAPS–PR constitutes a valid instrument to analyze perfectionism in children from the parents' perspective.